2012
DOI: 10.1152/jn.00524.2012
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and dendritic GABAB receptors regulate neuronal excitability via different mechanisms

Abstract: Breton J-D, Stuart GJ. Somatic and dendritic GABA B receptors regulate neuronal excitability via different mechanisms. J Neurophysiol 108: 2810 -2818, 2012. First published September 5, 2012 doi:10.1152/jn.00524.2012.-GABA B receptors play a key role in regulating neuronal excitability in the brain. Whereas the impact of somatic GABA B receptors on neuronal excitability has been studied in some detail, much less is known about the role of dendritic GABA B receptors. Here, we investigate the impact of GABA B r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
(50 reference statements)
0
23
0
Order By: Relevance
“…To investigate the possibility that somatic and dendritic GABA B receptors have different sensitivity to tertiapin‐Q, we also tested the impact of tertiapin‐Q on dendritic GABA B responses in layer 5 pyramidal neurons during bath applications of baclofen (20 μ m ). These experiments showed that dendritic input resistance ( R n ) measured between 300 and 500 μm from the soma ( n = 5; average: 436 ± 13 μm) decreased significantly from 26.4 ± 1.5 MΩ in control to 19.8 ± 1.5 MΩ in the presence of baclofen ( n = 5; P < 0.05), as previously described (Breton & Stuart, ). Concomitant application of tertiapin‐Q (100 n m ) with baclofen failed to block the impact of baclofen on dendritic input resistance ( R n baclofen + tertiapin‐Q: 19.4 ± 1.9 MΩ; n = 5, P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the possibility that somatic and dendritic GABA B receptors have different sensitivity to tertiapin‐Q, we also tested the impact of tertiapin‐Q on dendritic GABA B responses in layer 5 pyramidal neurons during bath applications of baclofen (20 μ m ). These experiments showed that dendritic input resistance ( R n ) measured between 300 and 500 μm from the soma ( n = 5; average: 436 ± 13 μm) decreased significantly from 26.4 ± 1.5 MΩ in control to 19.8 ± 1.5 MΩ in the presence of baclofen ( n = 5; P < 0.05), as previously described (Breton & Stuart, ). Concomitant application of tertiapin‐Q (100 n m ) with baclofen failed to block the impact of baclofen on dendritic input resistance ( R n baclofen + tertiapin‐Q: 19.4 ± 1.9 MΩ; n = 5, P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicate that presynaptic GABA B receptors downregulate voltage-activated calcium channels, restricting neurotransmitter release from synaptic terminals (Scholz & Miller, 1991;Campbell et al, 1993;Mintz & Bean, 1993). Postsynaptic GABA B receptors can also modulate voltage-activated calcium channels in dendrites and spines (Kavalali et al, 1997;Sabatini & Svoboda, 2000;Chalifoux & Carter, 2011), where they regulate dendritic excitability and neuronal output both in vitro and in vivo (Perez-Garci et al, 2006;Breton & Stuart, 2012;Palmer et al, 2012). GABA B receptors also regulate neuronal excitability via the activation of potassium channels leading to a slow membrane hyperpolarization, first identified in hippocampal neurons (Gahwiler & Brown, 1985;Newberry & Nicoll, 1985;Luscher et al, 1997;Chen & Johnston, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Addressing inhibition of Ca 2+ processes more directly, a number of elegant studies have described dendritic inhibition of Ca 2+ -dependent spikes upon activation of single (Larkum et al, 1999) or multiple (Miles et al, 1996;Tsubokawa and Ross, 1996) dendrite-targeting inhibitory interneurons in brain slices, as well as in vivo (Murayama et al, 2009). On top of GABA A -dependent effects, some of this inhibition is also mediated by GABA B receptor activation (Pé rez-Garci et al, 2006Chalifoux and Carter, 2011;Breton and Stuart, 2012). On a population level, dendritic inhibition acts as a key regulator of neuronal input-output transformations (Lovett-Barron et al, 2012;Mü ller et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the specific mechanism by which the pAkt pathway affects neuronal differentiation in AEM ion‐treated PC12 cells is ambiguous, some studies have suggested that Akt could be phosphorylated to pAkt through Ca‐ion channel stimulation . In the case of the Ba 2+ ion, its ability to pass through a potassium‐ion channel and a Ca‐ion channel may result in very high pAkt expression . Two other signaling pathways, pERK and pp38, are known to affect the neurite outgrowth of PC12 cells.…”
Section: Resultsmentioning
confidence: 99%